Autistic-Like Behavior and Impairment of Serotonin Transporter and AMPA Receptor Trafficking in N-Ethylmaleimide Sensitive Factor Gene-Deficient Mice - Xie, Min-Jue; Iwata, Keiko; Ishikawa, Yasuyuki; Nomura, Yuki; Tani, Tomomi; Murata, Koshi; Fukazawa, Yugo; Matsuzaki, Hideo (Frontiers in Genetics, 2021)
Autism spectrum disorder (ASD), characterized by profound impairment in social interactions and communication skills, is the most common neurodevelopmental disorder. Many studies on the mechanisms underlying the development of ASD have focused on the serotonergic system; however, these studies have failed to completely elucidate the mechanisms. We previously identified N-ethylmaleimide-sensitive factor (NSF) as a new serotonin transporter (SERT)-binding protein and described its importance in SERT membrane trafficking and uptake in vitro. In the present study, we generated NSF+/- mice and investigated their behavioral, neurotransmitter, and neurophysiological phenotypes in vivo. NSF+/- mice exhibited abnormalities in sociability, communication, repetitiveness, and anxiety. Additionally, NSF loss led to a decrease in membrane SERT expression in the raphe and accumulation of glutamate alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors at the synaptic membrane surface in the hippocampal CA1 region. We found that postsynaptic density and long-term depression were impaired in the hippocampal CA1 region of NSF+/- mice. Taken together, these findings demonstrate that NSF plays a role in synaptic plasticity and glutamatergic and serotonergic systems, suggesting a possible mechanism by which the gene is linked to the pathophysiology of autistic behaviors.